2017
DOI: 10.1186/s40852-017-0068-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of architectural knowledge and innovation

Abstract: Knowledge across several segments appears to be a necessary ingredient to innovation in the case of an architectural shift. Innovative firms utilize their knowledge stock to confront the competitive market. This paper demonstrates that exploitation of accumulated knowledge leads to architectural innovation. Ironically, in the new development of products with a short life cycle, when a firm discards its accumulated knowledge, innovation can be the result. After architecture technology is fully emerged, the util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…To respond to the challenge of managing radical innovation, firms tend to deepen technological collaborations with diverse partners. Han [32] implied that open innovation inherently involves the "quest of the unknown" territory of the knowledge frontier, alluding to a hidden connection to explorative innovation. Lausen and Salter [33] empirically tested the influence of open innovation on radical innovation.…”
Section: Ambidextrous and Balanced Innovation And Its Relation To Opementioning
confidence: 99%
See 1 more Smart Citation
“…To respond to the challenge of managing radical innovation, firms tend to deepen technological collaborations with diverse partners. Han [32] implied that open innovation inherently involves the "quest of the unknown" territory of the knowledge frontier, alluding to a hidden connection to explorative innovation. Lausen and Salter [33] empirically tested the influence of open innovation on radical innovation.…”
Section: Ambidextrous and Balanced Innovation And Its Relation To Opementioning
confidence: 99%
“…The breadth of open innovation, similar to [32], extracted from two questions from the KIS: the source of technological acquisition and on the partner type of technological collaboration The diversity of partner type is nine, thus ranging from 0 to 9. Open Innov.…”
Section: Openibreadth ←mentioning
confidence: 99%
“…For instance, the current research that found a relationship between fashion trendsetting and pro-environmental behaviors can be linked to emerging research topics, including how architectural trendsetters create imaginative architectural knowledge [67] or how trendsetters in various fields affect the dynamics from open innovation to evolutionary change [68]. Further research can also explore how business trendsetters develop novel business models for arts and cultural organizations [69], and how educational trendsetters can lead in creating innovative educational curriculum [70].…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…In particular, securing the competitiveness of state-owned commercial banks is a prerequisite for the successful reform of the Chinese banking system since they are the most important players in terms of asset size and credit share in the Chinese financial industry. The state-owned commercial banks account for 54% of the total assets of the financial institutions in China, and thus they occupy an exclusive position in the financial industry [1][2][3]. Therefore, the government is mainly engaged in state-owned commercial banks to intervene and reform the banking system [4].…”
Section: Introductionmentioning
confidence: 99%